Zone-oriented defence in professional soccer matches: Does it really work? - Tenga, A. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The zone-oriented defence is based on the defensive organization that emphasizes on exerting pressure on the opponent player with the ball, at the same time providing backup and cover once the team loses ball possession in open play (Olsen et al., 1994). The empirical evidence for whether these guidelines really work is rarely found in the literature. The aim of this study is to examine the effects of defensive pressure, defensive backup and defensive cover, separately and combined, on the probability of conceding a goal in real matches from Norwegian professional male soccer. Methods A multidimensional qualitative analysis was performed on a total of 1891 team possessions. These included 203 goals (cases) and 1688 random team possessions (control group) from 163 matches played in the Norwegian professional male league during the 2004 season. Four categorical variables included three independent variables defensive pressure, defensive backup, and defensive cover and one dependent variable possession outcome were used. In addition, a variable overall defensive score was made from the combined probability scores of the three defensive variables. Their reliability based on inter-observer tests showed good and fair kappa values ( ) for two variables each. The association between the independent variables and the probability of conceding a goal was tested by univariate logistic regression analyses. We used an alpha value of < 0.05. Results & Discussion Results showed that imbalanced defence (loose pressure, absent backup, and absent cover) had a higher probability of conceding a goal than balanced defence (tight pressure, present backup, and present cover) (P<0.001) (Table 1). Conclusion The zone-oriented defence appear to be effective in preventing goals in real matches from Norwegian elite soccer.